Mewujudkan Lingkungan Sekolah Ramah Lingkungan: Implementasi Program Adiwiyata Di MAN 1 Gresik - Fatih Ahmad, Nur; Widodo, Lestari; Roifatul Umah, Ria; Nur Khofifah, Sinta (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2024)
Against the backdrop of the need for environmental awareness among students, schools are increasingly turning towards the principles of sustainability and nature conservation. Through a holistic approach, this research explores the concrete steps taken by schools to achieve the Adiwiyata title. This research is entitled Realizing an Environmentally Friendly School Environment: Implementation of the Adiwiyata Program at MAN 1 Gresik. This research discusses the efforts and strategies implemented by the school in realizing an environmentally friendly school environment through the implementation of the Adiwiyata Program. By using a qualitative descriptive method. In this context, the research highlights the important role of all stakeholders, including students, teachers, school staff, and parents, in realizing a sustainable school environment. Waste management strategies, energy saving, and the inculcation of environmental awareness values in the education curriculum are the main focus of this research. In addition, the implementation of green technology innovations and the involvement of the surrounding community are also an integral part of the efforts to realize Adiwiyata schools. The school's success in achieving the Adiwiyata title not only reflects concern for the environment, but also creates an inspiring and sustainable learning environment for the next generation